The effect of Transcranial Direct-Current Stimulation on M1 with and without Mirror Visual Feedback on Range of Motion and Hand Grip Strength of the affected upper limb in children with Spastic Hemiplegic Cerebral Palsy. - farzamfar, pegah; Heirani, Ali; Amiri, Ehsan; Sedighi , Mustafa; Daniel Gomes da Silva, Machado (Iranian Journal of Child Neurology, 2024)
Objectives This study investigated the effects of transcranial direct current stimulation (tDCS) before and during the mirror visual feedback (MVF) on hand grip strength (HGS) and range of motion of the affected hand in children with spastic hemiplegia cerebral palsy (SHCP). Materials & Methods Twelve children with SHCP participated in this randomized, crossover, and double-blind study. They were randomly exposed to one of four intervention conditions, including 1) a-tDCS-offline, 2) s-tDCS-offline, 3) a-tDCS-online, and 4) s-tDCS-online, with a one-week interval. Participants in the online condition received either anodal or sham tDCS during MVF, while those in the offline condition received tDCS before performing MVF. The tDCS was applied over the M1 area of the affected hemisphere for 20 minutes at 1 mA intensity. The HGS and range of motion of the wrist and elbow (ROM-W and ROM-E) of the affected limb were measured before (pre) and immediately after (post) interventions in each session. Results The results showed that the HGS was significantly higher under a-tDCS-offline (p=0.001), s-tDCS-offline (p=0.004), and s-tDCS-online (p=0.005) compared to the a-tDCS-online. Moreover, the ROM-W was significantly higher under a-tDCS-offline (p=0.034), s-tDCS-offline (0.011), and s-tDCS-online (p=0.027) compared to the a-tDCS-online. Eventually, the ROM-E was significantly higher under a-tDCS-offline, s-tDCS-offline, and s-tDCS-online compared to the a-tDCS-online (p˂0.001; p˂0.001; p=0.01, respectively). Conclusion The results might have practical implications regarding the timing of the application of tDCS in conjunction with MVF in children with SHCP.